2013
DOI: 10.1590/0103-6440201302241
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Flexural Strength of Commercially Pure Titanium Submitted to Laser and Tungsten Inert Gas Welds

Abstract: This study evaluated the tensile and flexural strength of tungsten inert gas (TIG) welds in specimens made of commercially pure titanium (CP Ti) compared with laser welds. Sixty cylindrical specimens (2 mm diameter x 55 mm thick) were randomly assigned to 3 groups for each test (n=10): no welding (control), TIG welding (10 V, 36 A, 8 s) and Nd:YAG laser welding (380 V, 8 ms). The specimens were radiographed and subjected to tensile and flexural strength tests at a crosshead speed of 1.0 mm/min using a load cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…TIG welding process involves joining metal structures by heating and melting them through an electric arc established between a tungsten electrode and the parts to be fused 16 . The most commonly used gases during TIG welding are helium and argon 10,17 . Although the use of TIG welding in dentistry is uncommon, some studies show the superiority of this technique compared to conventional brazing 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…TIG welding process involves joining metal structures by heating and melting them through an electric arc established between a tungsten electrode and the parts to be fused 16 . The most commonly used gases during TIG welding are helium and argon 10,17 . Although the use of TIG welding in dentistry is uncommon, some studies show the superiority of this technique compared to conventional brazing 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…An acrylic device containing a channel was used for accommodating the specimens, without any spaces between them 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Although the conventional brazing technique is more used in dentistry, studies have demonstrated the superiority of tungsten inert gas (TIG) welding 15,16 . This process uses an electric arc formed between a non-consumable tungsten electrode and the part to be fused and applies an inert gas (argon or helium) to provide local protection to prevent oxidation [17][18][19][20] . In this type of welding, heating is concentrated and disorders and deformation are minimized; furthermore, there is an increase in corrosion resistance due to the lack of galvanic effects in the joint 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies focused on prosthetic frameworks were developed to optimize their production by the use of prefabricated bars and welding techniques other than conventional welding (Lyra e Silva, et al 2012;Silveira-Júnior, et al 2012;Castro, et al 2015;Simamoto-Júnior, et al, 2015). Studies have been conducted to evaluate the types of welding techniques (Wang & Welsch, 1995;Baba & Watanabe, 2005;Rocha, et al 2006;Zupancic, et al 2006;Barbi, et al 2012;Lyra e Silva, et al 2012;Nuñez-Pantoja, et al 2012;Atoui, et al 2013;Castro, et al 2013;Castro, et al 2015;Matos, et al 2015;, the settings of welding equipment (Chai & Chou, 1998;Baba & Watanabe, 2005;Akman, et al 2009; Lyra e Silva, et al 2015), the types of alloys used (Rocha, et al 2006;Watanabe & Topham, 2006;Takayama, et al 2012;Takayama, et al 2013;Lyra e Silva, et al 2015;Matos, et al 2015), the settings of the joints (Zupancic, et al 2006;Nuñez-Pantoja, et al 2012;Takayama, et al 2012;Kokolis, et al 2015;Simamoto-Júnior, et al 2015), and mechanical methods of evaluation of these weld joints (Nuñez-Pantoja, et al 2011;Takayama, et al 2012;Takayama, et al 2013;Castro, et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the welding techniques, two have been identified for dental use: laser welding (Berg, et al 1995;Wang and Welsch, 1995;Chai & Chou, 1998;Baba & Watanabe, 2005;Akman, et al 2009;Byrne, 2011;Nuñez-Pantoja, et al 2011;Barbi, et al 2012;Nuñez-Pantoja, et al 2012;Silveira-Júnior, et al 2012;Takayma, et al 2012;Atoui, et al 2013;Castro, et al 2013;Takayama, et al 2013;Castro, et al 2015;Kokolis, et al 2015;Matos, et al 2015) and TIG or plasma welding (Wang & Welsch, 1995;Taylor, et al 1998;Rocha, et al 2006;Byrne, 2011;Barbi, et al 2012;Lyra e Silva, et al 2012;Nuñez-Pantoja, et al 2012;Silveira-Júnior, et al 2012;Atoui, et al 2013;Castro, et al 2013;Castro, et al 2015;Matos, et al 2015;Simamoto-Júnior, et al 2015). Both have some advantages: welding can be performed directly on the model (Chai & Chou, 1998;Baba & Watanabe, 2005;Rocha, et al 2006;Zupancic, et al 2006;Barbi, et al 2012;Silveira-Júnior, et al 2012;Castro, et al 2015), energy can be concentrated in a small area (Rocha, et al 2006;Barbi, et al 2012;Lyra e Silva, et al 2012;…”
Section: Introductionmentioning
confidence: 99%